2018
DOI: 10.3390/w10081103
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations in the Abundance and Chemical Speciation of Phosphorus across the River–Sea Interface in the Northern Beibu Gulf

Abstract: Water samples were collected to measure dissolved and particulate phosphorus species in order to examine the dynamics of phosphorus in the water column across the river–sea interface from the lower Dafengjiang River to the open Beibu Gulf. Dissolved inorganic phosphorus concentrations were as high as 0.90 ± 0.42 μM in river water but decreased dramatically to as low as 0.02 ± 0.01 μM in open coastal waters. Total dissolved phosphorus was largely measured in the form of dissolved inorganic phosphorus in river w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…In the present research, Ex-P contribute the lowest to TP (4%), as was also found in Jiaozhou Bay [23], the East China Sea Shelf [24], Maowei Sea in the Beibu gulf [25], and Changjiang Estuary [26]. The average concentration (15 µg/g) was also in a similar range to these estuaries and bays (Table 4), but it was much lower than that in South China Sea [27], south Long Island (USA) [28], Kalpakkam( India) [29], southern Caspian Sea [21], and the eastern coast of Hainan Island [30] (Table 4). Relatively high values of Ex-P were generally related to a high input of phosphate from the rivers or coastal sewage, such as in the Pearl River, Changjiang River, and Wanquan Rive [27,[30][31][32].…”
Section: Phosphorus Speciessupporting
confidence: 80%
See 1 more Smart Citation
“…In the present research, Ex-P contribute the lowest to TP (4%), as was also found in Jiaozhou Bay [23], the East China Sea Shelf [24], Maowei Sea in the Beibu gulf [25], and Changjiang Estuary [26]. The average concentration (15 µg/g) was also in a similar range to these estuaries and bays (Table 4), but it was much lower than that in South China Sea [27], south Long Island (USA) [28], Kalpakkam( India) [29], southern Caspian Sea [21], and the eastern coast of Hainan Island [30] (Table 4). Relatively high values of Ex-P were generally related to a high input of phosphate from the rivers or coastal sewage, such as in the Pearl River, Changjiang River, and Wanquan Rive [27,[30][31][32].…”
Section: Phosphorus Speciessupporting
confidence: 80%
“…The average concentration (15 µg/g) was also in a similar range to these estuaries and bays (Table 4), but it was much lower than that in South China Sea [27], south Long Island (USA) [28], Kalpakkam( India) [29], southern Caspian Sea [21], and the eastern coast of Hainan Island [30] (Table 4). Relatively high values of Ex-P were generally related to a high input of phosphate from the rivers or coastal sewage, such as in the Pearl River, Changjiang River, and Wanquan Rive [27,[30][31][32]. The research indicates that organic matter may also be an important factor regulating the Ex-P concentration because of the high correlation of Ex-P with TOC contents [2,23].…”
Section: Phosphorus Speciesmentioning
confidence: 71%
“…The high percentage of Ca-P indicates that the sediment in the study area does not significantly contribute to the addition of dissolved P concentration in the water column and does not directly affect the eutrophication. This is different if the highest fraction is found in Fe-P, which is often used as an indicator of polluted waters (Vicente et al, 2016;Yang et al, 2018). The percentage of each fraction of P to the P total (TP) is presented in Figure 2.…”
Section: The Fraction Of P In Sedimentsmentioning
confidence: 98%
“…Several studies on the phosphorus fraction in sediments have been carried out in China (Yang et al, 2018;Kang et al, 2017;Zhou et al, 2016) and Brazil (Vicente et al, 2016) and Japan (Yamada & Kayama, 1987). Research on the P fraction in Indonesia has been conducted previously by Maslukah et al (2019a), in areas far from the mainland.…”
Section: Introductionmentioning
confidence: 99%
“…At the estuary, where mixing of fresh water and seawater occurs, spatial and seasonal variations in the availability of N and P causes nutrient limitations, which causes difficulties for prioritising the nutrient management [1,6]. Phosphorus (P) is an essential nutrient that plays a main role in biogeochemical cycles of coastal environments [7,8]. Sediments in the marine environment play as important buffering and reservoirs of P content and are important sources in the over laying water [9].…”
Section: Introductionmentioning
confidence: 99%